Structural, mechanical, and gas barrier properties of poly(ethylene terephthalate) nanohybrid using nanotalc - Saxena D.; Soundararajan N.; Katiyar V.; Rana D.; Maiti P. (My University, 2025)
Amorphous poly(ethylene terephthalate) (PET)/nanotalc nanohybrids have been prepared through solution casting route. The fine dispersion of nanotalc clay in the polymer matrix has been examined through transmission electron microscopy (TEM). The intercalation and interaction of nanoclay have further been confirmed using X-ray diffraction, ultraviolet, and Fourier transform infrared techniques. The thermal stability has been tested via thermogravimetric analysis and nanohybrids have been found thermally stable. The glass-transition temperature has been further confirmed through DTA and differential scanning calorimetry analysis which has been increased in the presence of nanotalc arising from greater interaction. The nanohybrids have been tested for their mechanical performances and have been found to have improved mechanical responses for nanotalc-filled nanohybrids. The modulus has been increased whereas toughness has been compromised meagerly. The modulus values have been theoretically predicted using various micromechanical models. The microhardness of the nanohybrids has been examined through Vicker hardness test. The theoretical prediction of the hardness values has been done using different micromechanical models. The structural development upon uniaxial stretching of the samples has been studied using small-angle X-ray scattering and wide-angle ray diffraction. The stretched samples have found to have short-range ordering as well as increased blob size and better coherency in the presence of nanotalc. The aspect ratio has been increased upon stretching. The inclusion of nanotalc has induced high barrier for gas permeation as compared to pure PET. The oxygen transmission rate has been found to decrease up to 64% for 8 wt % of filler concentration. The prediction of the permeability data has been done using different models considering different aspect ratios. The permeability values have been predicted very closely and nanohybrids have been found suitable for practical applications such as packaging. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48607. © 2019 Wiley Periodicals, Inc.